Live 3-D video in volumetric display - Son, JY; Shestak, SA; Huschyn, VP; Ulizko, VA; Kang, DH (STEREOSCOPIC DISPLAYS AND VIRTUAL REALITY SYSTEMS IX, 2002)
A live volumetric image is created from a plane image taken by a CCD camera with the aid of depth-wise segmented images from a high-speed B/W camera. The segmented images are obtained by a rotating screen in the image volume of an objective with a large aperture objective. By processing the output signal from th e B/W camera, the boundary of each segmented image from the camera is extracted. This boundary information is used to control the frame size of CCD camera image, which is projected through CRT projector to another rotating screen to generate volumetric image. The rotating screen displays image with frame speed of 30Hz. Each volumetric image is consisted of 8 layers. The rotating screen has a form of rotating cylinder with 8 slanted leaves along its circumference with an equal distance.